Solar energy harvesting using lead-free pyroelectric bulk ceramics: a simulation study - Saurabh, Nishchay (2023)
Solar radiation and wind provide the temporal temperature fluctuation for heating and cooling. 0.005La–Na0.5Ba0.5TiO3-0.06BaTiO3-0.002Ta is found as the best suitable material for energy harvesting. The voltage and power output are further improved by tuning operating frequency, load capacitance and resistance. Maximum power of 6.7 μW is obtained at a frequency of 0.04 Hz, load capacitance of 1 μF and resistance of 25 MΩ. A nonlinear electrical circuit based on parallel synchronized switched harvesting on the inductor (P–SSHI) and hybrid synchronized switched harvesting on the inductor (H–SSHI) are used to enhance the power. The power is increased by 54% and 34.6% under P–SSHI and H–SSHI, respectively. However, H–SSHI was preferred for power-boosting because of the self-triggering process and low energy losses. This work shows the potential of lead-free pyroelectric materials for solar energy harvesting with losses in the circuit.